2019
DOI: 10.22226/2410-3535-2019-4-556-560
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing parameters on the mechanical properties of heterogeneous lamella structured 5083 aluminum alloy

Abstract: It has long been a research goal to obtain both high strength and ductility in structural materials. As the most important structural materials, metals and alloys are either strong or ductile, but seldom maintain both characteristics at the same time. After decades of attempts, extraordinary high strength has been achieved by involving nano-or ultrafine-grained structure. However, the ductility of these materials is relatively low. In the recent years, heterostructured materials have been demonstrated to posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…[20]. In another study X. Fang et al reported R values for Al 5083 in annealed condition at 0°, 45° and 90° to the rolling direction [21]. In formability analysis effect of temperature and strain rate is reported that with increase in temperature of Al5052, Al 5086 andAl6061 sheets.…”
Section: Tensile Test Resultsmentioning
confidence: 97%
“…[20]. In another study X. Fang et al reported R values for Al 5083 in annealed condition at 0°, 45° and 90° to the rolling direction [21]. In formability analysis effect of temperature and strain rate is reported that with increase in temperature of Al5052, Al 5086 andAl6061 sheets.…”
Section: Tensile Test Resultsmentioning
confidence: 97%
“…Several fabrication methods have been introduced to offer various heterogeneous structured materials with balanced strength and ductility, such as the gradient structure produced by surface mechanical attrition [ 11 , 12 , 13 ], the hetero-lamellar structure produced by cold rolling and annealing [ 2 , 14 , 15 ], and the harmonic structure produced by powder metallurgy [ 16 , 17 , 18 , 19 , 20 ]. Mechanical milling, a metallurgy technique, has been applied for microstructure modification [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%